Careful Dissection of the Distal Ureter Is Highly Important in Nerve-sparing Radical Pelvic Surgery: A 3D Reconstruction and Immunohistochemical Characterization of the Vesical Plexus. Issue 5 (June 2016) - Kraima, Anne C.; Derks, Marloes; Smit, Noeska N.; van de Velde, Cornelis J.H.; Kenter, Gemma G.; DeRuiter, Marco C.
Abstract : Objective: Radical hysterectomy with pelvic lymphadenectomy (RHL) is the preferred treatment for early-stage cervical cancer. Although oncological outcome is good with regard to recurrence and survival rates, it is well known that RHL might result in postoperative bladder impairments due to autonomic nerve disruption. The pelvic autonomic network has been extensively studied, but the anatomy of nerve fibers branching off the inferior hypogastric plexus to innervate the bladder is less known. Besides, the pathogenesis of bladder dysfunction after RHL is multifactorial but remains unclear. We studied the 3-dimensional anatomy and neuroanatomical composition of the vesical plexus and describe implications for RHL. Materials and Methods: Six female adult cadaveric pelvises were macroscopically dissected. Additionally, a series of 10 female fetal pelvises (embryonic age, 10–22 weeks) was studied. Paraffin-embedded blocks were transversely sliced in 8-μm sections. (Immuno) histological analysis was performed with hematoxylin and eosin, azan, and antibodies against S-100 (Schwann cells), tyrosine hydroxylase (postganglionic sympathetic fibers), and vasoactive intestinal peptide (postganglionic parasympathetic fibers). The results were 3-dimensionally visualized. Results: The vesical plexus formed a group of nerve fibers branching off the ventral part of the inferior hypogastric plexus to innervate the bladder. In all adult and fetal specimens, the vesical plexus was closely related to the distal ureter and located in both the superficial and deep layers of the vesicouterine ligament. Efferent nerve fibers belonging to the vesical plexus predominantly expressed tyrosine hydroxylase and little vasoactive intestinal peptide. Conclusions: The vesical plexus is located in both layers of the vesicouterine ligament and has a very close relationship with the distal ureter. Complete mobilization of the ureter in RHL might cause bladder dysfunction due to sympathetic and parasympathetic denervation. Hence, the distal ureter should be regarded as a risk zone in which the vesical plexus can be damaged.